Robot-assisted radical prostatectomy in prostate cancer. (October 2015) - Gandaglia, Giorgio; Montorsi, Francesco; Karakiewicz, Pierre I; Sun, Maxine
Since its introduction in the year 2000, robot-assisted radical prostatectomy (RARP) rapidly diffused, and nowadays roughly 70% of all the radical prostatectomies in the USA are performed using this approach. Interestingly, the broad dissemination of RARP occurred in the absence of comprehensive data coming from prospective randomized trials supporting the superiority of RARP versus the conventional open RP (ORP). Only observations originating from retrospective institutional or large population-based cohorts exist with respect to the comparative effectiveness of the two surgical techniques. What we have learned is that, given an adequate learning curve, RARP leads to better perioperative and long-term functional outcomes compared with ORP, without any compromise to cancer control outcomes. That being said, the substantially higher costs associated with the use of robotics cannot be ignored.